Ready2Change: Preliminary effectiveness of a telephone‐delivered intervention program for alcohol, methamphetamine and cannabis use problems. (3rd August 2021) - Grigg, Jasmin; Volpe, Isabelle; Tyler, Jonathan; Hall, Kate; McPherson, Belinda; Lubman, Dan I.; Manning, Victoria
Abstract: Introduction: Telehealth has considerable potential to overcome many of the barriers to accessing care for substance use problems, thereby increasing the opportunity for earlier intervention. The Ready2Change program is a multiple‐session outbound telephone‐delivered cognitive and behavioural intervention for mild‐to‐moderate substance use disorders, embedded within a long‐established 24/7 alcohol and drug helpline. We sought to analyse routinely collected program data in a preliminary study to examine the effectiveness of Ready2Change in reducing substance use problem severity and psychological distress. Methods: A retrospective analysis of program data from December 2013 to June 2018 was performed. Analysed cases were 249 clients living in Victoria, Australia with alcohol ( n  = 191), methamphetamine ( n  = 40) or cannabis ( n  = 18) as their primary drug of concern. A within‐subjects design was used to examine pre‐ and post‐intervention substance use problem severity and psychological distress. Results: For alcohol cases, there was a statistically significant decrease in alcohol problem severity [AUDIT, mean difference = −12.7, 95% confidence interval (CI) −14.0, −11.5]. Statistically significant reductions in drug problem severity (DUDIT) were observed for methamphetamine (mean difference = −17.3, 95% CI −20.9, −13.7) and cannabis (mean difference = −15.9, 95% CI −22.3, −9.6) cases. All groups showed reductions in problem severity for other substances used ( P  < 0.05) and psychological distress ( P  < 0.001). Discussion and Conclusions: Results suggest Ready2Change benefits clients with alcohol, methamphetamine and cannabis use problems, with the potential to improve treatment access for health inequity groups including those living in remote areas. These findings warrant further investigation into the effectiveness of this program.